Oral anti‐CD3 immunotherapy for HCV‐nonresponders is safe, promotes regulatory T cells and decreases viral load and liver enzyme levels: results of a phase‐2a placebo‐controlled trial. Issue 8 (21st November 2014) - Halota, W.; Ferenci, P.; Kozielewicz, D.; Dybowska, D.; Lisovoder, N.; Samira, S.; Shalit, I.; Ellis, R.; Ilan, Y.
Summary Orally administered anti‐CD3 antibodies are biologically active in the gut through induction of regulatory T cells, exert an immune‐modulatory effect, and alleviate insulin resistance and liver damage in patients with NASH. Aims: To determine the safety of oral anti‐CD3 monoclonal antibody (MAb) immunotherapy in chronic HCV patients with associated immune dysfunction. Methods: Four groups (n = 9) of chronic HCV patients who were nonresponders to interferon plus ribavirin therapy received oral placebo (group A) or anti‐CD3 MAb at one of three dosage levels for 30 days. Patients were followed for safety parameters and serum levels of liver enzymes, virus, cytokines and regulatory T cells. Results: Oral anti‐CD3 immunotherapy was safe and well tolerated; no treatment‐related adverse events were noted. The following improvements were noted relative to pretreatment levels: HCV viral load and AST and ALT levels decreased in the low‐ and high‐dose groups following 30 days of therapy. In two of the treated groups, an increase in regulatory T cells (CD4+ CD25+) was noted. The positive effects were somewhat more apparent in subjects with initially elevated liver enzyme levels. Conclusions: Oral anti‐CD3 MAb immunotherapy for nonresponder HCV patients was safe and well tolerated. Trends and statistically significant improvements were observed as reductions in viral load and liver enzyme levels, along with an increase in regulatory T‐cell levels. These data support a role for the immune system in the pathogenesis of HCV infection and suggest that this immunotherapy is worthy of evaluation in combination with HCV antiviral drugs.